Determinación del grado de actividad física e intención de cambio en niñas y niños que participaron en las Escuelas Deportivas y Recreativas del Verano del 2005 de la Universidad de Costa Rica - Chacón Araya, Yamileth (2006)
The aim of the study was to assess the levels of physical activity and potential for behavior change among children and youth who participated in a structured summer camp program in physical activity and sports at the University of Costa Rica. Participants were 113 subjects with an age range between 8 and 16 years. Subjects responded to a “Stages of Change” questionnaire, and also to items regarding habitual physical activity, and opportunities for becoming physically-active. Statistical analysis showed that 80.5% of the participants exercised regularly (i.e., for at least for three consecutive months). It was estimated that 50.4% of the participants did not have the opportunity to play outdoors without parental and/or legal supervision, and that about 91.2% considered important to exercise along with their parents. From the sample studied, it was found that 94.7% had consistently received only one or two formal Physical Education classes throughout their lives; which might impact their future physical and psychological health and their possibilities to achieve a desired exercise adherence. Only 67.3% of the participants were classified in a stage based on the Stages of Change Model for physical activity, with 55.8% from those belonging to the maintenance stage. This is the first attempt to investigate the intention to change in Costa Rica children; however, the results from the present study are consistent with those reported in other countries. In conclusion, the Transtheoretical Model Behavior Change might be appropriate to detect disposition to change from detrimental behaviors towards a positive and healthy lifestyle in children and adolescents. Further research is needed to study moderator variables that might impact behavior changes in this population.